Factors Affecting Entrepreneurship Behavior: Variance-Based Structural Equation Modelling - Firman Firman; Firscilla Wulan Tersta; Felicia Ayu Sekonda; Hidayatul Arief; Budi Setiawan (Indonesian Journal Of Educational Research and Review, 2022)
Entrepreneurship is widely recognized as one of the important elements for achieving success in today’s society because of its important contribution to economic growth, job creation, and technological advancement. This study aims to analyze empirically the effect of the interaction between entrepreneurial intentions (EI) and entrepreneurial behaviour (EB), which is influenced by determinants such as competitive nature, keen attention to entrepreneurship, and proactive personality. This study used a quantitative approach with a cross-sectional survey design. A total of 2322 students who were about to graduate were involved in this study. Attention sharpness in entrepreneurship was measured using 13-items questions. The competitive trait was measured using three items. Proactive personality was measured using ten items. Entrepreneurial Intentions was measured using the entrepreneurial intention scale, namely personal attitudes, subjective norms, and perceived behavioural control. PLS-SEM was used at the stage of model measurement and hypothesis testing. The results of the study inform that the four hypotheses of the antecedent variable directly influence entrepreneurial intentions and behaviour. Still, there is no moderation in the competitive trait and proactive personality variables in the two hypotheses. Students’ awareness of the need for achievement and the personality characteristics required for entrepreneurship can change when they are brought into direct experience with entrepreneurs who can be role models.